(untitled) - Creswell, John W. (London, 2015)
A Concise Introduction to Mixed Methods Research is a brief overview of mixed methods research that takes readers through the essential steps in planning and designing a study. Rather than offering an extensive treatment of mixed methods, this concise book offers individuals in the social, behavioral, and health sciences a foundation for understanding mixed methods methodology. Practical for use in workshops, seminars, global webinars, and as a supplementary text in undergraduate and graduate classes, Creswell’s book is ideal for the beginner or the more advanced researcher looking for a quick primer in mixed methods, by an authoritative mixed methods scholar.
Keywords: Nghiên cứu,Research; Phương pháp luận,Methodology